Precision measurement system and analysis of low core signal loss in DCF couplers. (9th June 2016) - Yan, P; Wang, X J; Fu, Ch; Li, D; Sun, J Y; Gong, M L; Xiao, Q R
Abstract: In order to achieve higher output power of double cladding fiber lasers, low signal loss has become a focus in researches on optical technology, especially double-clad fiber (DCF) couplers. According to the analysis, DCF couplers with low core signal loss (less than 1%) are produced. To obtain higher precision, we use the first-proposed method for core signal transfer efficiency measurement based on the fiber propagation field image processing. To the best of our knowledge, we report, for the first time, the results of the core signal loss less than 1% in DCF coupler measured by our measurement with high stability and relative precision. The measurement values can assess the quality of DCF couplers and be used as a signal to suggest the improvement on the processing technology of our self-made DCF couplers.